1968
DOI: 10.1002/ijc.2910030513
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome studies on cultured lymphoblast cell lines from cases of new guinea burkitt lymphoma, myeloblastic and lymphoblastic leukaemia and infectious mononucleosis

Abstract: Chromosome analysis of three lymphoblast cell lines from New Guinea Burkitt lymphoma (QIMR‐GOR, QIMR‐AMB/1 and AMB/2), three lymphoblast cell lines from infectious mononucleosis (QIMR‐DAR, QIMR‐STE and QIMR‐GOE) and two lymphoblast cell lines from leukaemia (QIMR‐WIL and QIMR‐FIN) showed abnormalities associated with Group A, C, and G chromosomes. Each cell line contained diploid and near diploid cells. Some of the cell lines also contained pseudodiploid cells. Extra Group C or Group G chromosomes were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A similar abnormality was also found in lymphoid lines (LCL) from other sources, however (Kohn et al, 1968;Pope et al, 1968;Chessin et al, 1968;Miles et al, 1968;Macek and Benyesh-Melnick, 1969). In other studies with EBV-carrying LCL cells this marker was only found in a minority of the lines and in a small proportion of the metaphases (Tomkins, 1968;Saksela and PontCn, 1968;Huang et al, 1970;Whang-Peng et a/., 1970).…”
mentioning
confidence: 83%
“…A similar abnormality was also found in lymphoid lines (LCL) from other sources, however (Kohn et al, 1968;Pope et al, 1968;Chessin et al, 1968;Miles et al, 1968;Macek and Benyesh-Melnick, 1969). In other studies with EBV-carrying LCL cells this marker was only found in a minority of the lines and in a small proportion of the metaphases (Tomkins, 1968;Saksela and PontCn, 1968;Huang et al, 1970;Whang-Peng et a/., 1970).…”
mentioning
confidence: 83%
“…Previous cytogenetic studies on infectious mononucleosis (IM) have mainly been undertaken in long-term lymphocyte cultures (Tomkins 1968), which are comparatively easy to establish from subjects with previous exposure t o Epstein-Barr virus (EBV), now recognised as the causative agent in IM (Klein 1973). Direct chromosome analyses, on the other hand, have been hampered by the reduced susceptibility of IM lymphocytes to the mitogen phytohaemagglutinin (Rassiga Pidot et al 1973).…”
mentioning
confidence: 99%